Implementation P5 Based Green Innovation For Increase Attitude Care Environment - Windi Masmodah; Ristiana Dyah Purwandari (UM Purwokerto Press, 2025)
This study aims to improve students' attitudes of care for the environment through the implementation of green innovation based on the Pancasila Student Profile Strengthening Project (P5) at Sidamukti 03 Patimuan Elementary School, Cilacap. The research employed a Classroom Action Research (CAR) method conducted in three cycles, each consisting of planning, implementation, observation, and reflection. The study involved 20 third-grade students participating in green innovation activities such as creating a classroom mini garden, a creative recycling program, and weekly Green Day actions. The results demonstrated a significant increase in students’ environmental awareness, rising from 35% in the pre-cycle to 90% by the end of the third cycle. These findings suggest that integrating green innovation within the P5 framework effectively enhances students’ attitudes of care toward the environment in a sustainable and meaningful way.